Functional communication training during reinforcement schedule thinning: An analysis of 25 applications. Issue 1 (20th October 2015) - Greer, Brian D.; Fisher, Wayne W.; Saini, Valdeep; Owen, Todd M.; Jones, Jamie K.
Abstract : Two principal goals of functional communication training (FCT) are (a) to eliminate destructive behavior and (b) to establish a more acceptable, yet functionally equivalent, communication response (FCR). A related and critically important goal is to thin the schedule of reinforcement for the FCR to levels that can be reasonably managed by caregivers. Researchers have described several approaches to thinning FCT reinforcement schedules. We summarize the results of 25 consecutive applications (among 20 cases) in which schedule‐thinning procedures employed discriminative stimuli to signal when the FCR would and would not produce reinforcement (i.e., using multiple schedules, response restriction, or chained schedules). Results suggest that schedule‐thinning procedures that use discriminative stimuli can maintain the effectiveness of FCT while they minimize the need for punishment or other supplemental procedures.